Electron Cyclotron Resonance Chemical Vapour Deposition of SiOxNy Films for Use in Flat Panel Displays - Wood, Richard (My University, 2006)
Thin silicon based films were produced using low temperature (less than 60° C) electron cyclotron resonance plasma enhanced chemical vapour deposition (ECR PECVD). These films were examined for suitability in flat panel display applications. SiOxNy films were tested for use as insulating films in thin film electroluminescent (TFEL) devices. The ECR PECVD method was found to be suitable when the plasma was created using pure nitrogen (as opposed to argon) in high ratios to the silane precursor.
Hydrogenated silicon films were also produced and evaluated for their suitability as semiconductor layers in thin film transistors (TFTs). The silicon films were subject to nickel induced crystallization. The silicon films were found to crystallize at low temperatures, (<950° C) in the presence of nickel. These films were used to produce prototype metal insulator semiconductor (MIS) capacitors and TFTs.
Keywords: electron cyclotron, resonance, chemical, vapour deposition, films, flat panel, displays, silicon